Effect of achyranthes aspera L. on fetal abortion, uterine and pituitary weights, serum lipids and hormones - Shibeshi, Workineh (Makerere Medical School, 2006)
BACK GROUND: The practice of traditional medicine for the control of fertility in rural Ethiopia is based on folk use of numerous anti-fertility herbs and Achyranthes aspera is one of these used for this purpose. Many plants are known to possess anti-fertility effect through their action on hypothlamo-pituitary-gonadal axis or direct hormonal effects on reproductive organs resulting in inhibition of ovarian steroidogenesis. OBJECTIVES: The present study focused to investigate the effect of methanolic leaves extract of Achyranthes aspera L. on some indicators for anti-fertility activities such as abortifacient, estrogenesity, pituitary weight, and ovarian hormone level and lipids profile in female rats, in attempt to validate the traditional claim. METHODS: The abortifacient effect of the methanolic extract of the leaves of Achyranthes aspera was determined by counting the dead fetuses in vivo. Effect on estrogenesity was assessed by taking the ratio of the uterine weight to body weight. The ratio of the pituitary weight to body weight was also calculated. The effect of the extract on the level of ovarian hormones and lipid profile was evaluated using electrochemiluminescence immunoassay. RESULTS: The extract showed significant (p<0.05) abortifacient activity and increased pituitary and uterine wet weights in ovarectimized rats. The extract, however, did not significantly influence serum concentration of the ovarian hormones and various lipids except lowering HDL at doses tested. CONCLUSION: The methanolic leaves extract of Achyranthes aspera possesses anti-fertility activity, which might be exploited to prevent unwanted pregnancy and control the ever-increasing population explosion.